Effect of the ZrO2 phase on the structure and behavior of supported Cu catalysts for ethanol conversion - Sato, A. G.; Volanti, D. P. [UNESP]; Meira, D. M.; Damyanova, S.; Longo, Elson [UNESP]; Bueno, J. M C (Elsevier, 2013)
The effect of amorphous (am-), monoclinic (m-), and tetragonal (t-) ZrO2 phase on the physicochemical and catalytic properties of supported Cu catalysts for ethanol conversion was studied. The electronic parameters of Cu/ZrO2 were determined by in situ XAS, and the surface properties of Cu/ZrO2 were defined by XPS and DRIFTS of CO-adsorbed. The results demonstrated that the kind of ZrO2 phase plays a key role in the determination of structure and catalytic properties of Cu/ZrO 2 catalysts predetermined by the interface at Cu/ZrO2. The electron transfer between support and Cu surface, caused by the oxygen vacancies at m-ZrO2 and am-ZrO2, is responsible for the active sites for acetaldehyde and ethyl acetate formation. The highest selectivity to ethyl acetate for Cu/m-ZrO2 catalyst up to 513 K was caused by the optimal ratio of Cu0/Cu+ species and the high density of basic sites (O2-) associated with the oxygen mobility from the bulk m-ZrO2. © 2013 Elsevier Inc. All rights reserved.
Keywords: Characterization; Cu/ZrO2 catalysts; Ethanol dehydrogenation; Ethyl acetate; Catalytic properties; Electron transfer; Electronic parameters; Ethanol conversion; Ethyl acetates; Oxygen mobility; Supported Cu; Catalyst selectivity; Ethanol; Zirconium alloys; Catalyst supports